An experimental investigation of single lignite particle dried in superheated steam and hot air - Celen, P.; Erdem, H. H. (TAYLOR & FRANCIS INC, 2021)
In lignite (low-rank coal)-fired thermal power plants, thermal efficiency can be improved by decreasing the lignite moisture. The lignite moisture can be removed by using superheated steam and hot air as drying fluids. In this study, Turkish (Afsin-Elbistan) lignite having a diameter of 30 mm was dried with superheated steam and hot air at temperatures of 117 degrees C under atmospheric pressure. The changes in its weight and temperature with time were observed, and the drying characteristics were obtained during the drying process. In the first period of drying, which is called heating period, the drying rate of superheated steam is higher than hot air in contrary to during constant-rate period. Moreover, the experiments revealed that less time is required to heat lignite sample with superheated steam compared to hot air.
Keywords: Lignite drying; superheated steam; hot air; single particle drying; DRYING KINETICS; SIMULATION; BEHAVIOR; COALS; Energy & Fuels; Mining & Mineral Processing